Structural and magnetic properties of HoFeCuGe4O12 with a metamagnetic transition behavior - Xu, Diming; Liu, Zhibo; Li, Xiao; Avdeev, Maxim; Zhou, Ke-Hong; Li, Jun; Tan, KarBan; Zhou, Tao; Zhou, Di (Elsevier, 2025)
Metamagnetic materials exhibits great potential in applications such as magnetocaloric and colossal-magnetoresistance devices. This paper presents a structure and metamagnetic behavior study on HoFeCuGe4O12. Field-dependent susceptibility clarifies the antiferromagnetic (AFM) nature and the magnetization to magnetic field curve identifies the existence of metamagnetic behavior at ∼2 T. Structural studies, including X-ray diffraction, neutron diffraction and high-resolution transmission electron microscopy, reveals the magnetic structure to be an axial A-type AFM and the importance of cation anisotropy in metamagnetic behavior. The results provide an insight into manipulating metamagnetic transitions by cation anisotropy and structure characteristic.